A Gender-responsive approach to Community-Based Adaptation in Guinayangan, Quezon - Bayot, Ruvicyn; Palima, Carlo M.; Punzalan, Bermenito; Vidallo, Rene R.; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This study highlighted the importance of farmers’ understanding of the climate change effects, and identified recommendations on how to target women and enhance support services to increase the adaptive capacity of smallholder farmers. However, measures to increase women’s participation should be tailored to the local context. It would not be prudent to generalize recommendations for engaging women across different geographic, agroecological and socio-cultural contexts. Land tenure considerations must also be factored in planning the CSA interventions.